Hacia una comprensión del texto poético: a propósito de "Oda a la poesía" de Pablo Neruda - Jones León, Sonia (2006)
This article offers an approximation of the feeling engrossed in the differences of equivalent linguistic categories and the discovery of the diverse paths that constitute poetic text, which coincide with various discussions of human understanding.The "Oda a la poesía", as poetic text,  pursues the answer as to how a poem is constructed, both as a work and a poet from the stylistic point of view. Preliminary observations have determined the possibilities of the existence of isotopies ode that create these semantic groupings. Therefore, it is proposed, the discourse of this ode as bi- isotopic, and the manner of isotopy worldwide, the equivalencies drive the formation of the interweaving significance whose structure creates permanence-not the permanence of being, and going, the poem, much more than just a mere historical vision of its evolution.